Utilizing iSpring Suite to Develop MEDIFORA Android-Based Application as a Science Learning Media for Fourth Grade Elementary School Students - Rohmani, Rohmani; Utami , Purie Nawa (PT. Riset Press International, 2024)
The existence of the use of media in learning has been proven to be able to provide positive results on learning outcomes. The lack of learning media in accordance with the characteristics of the subject matter makes learning media rarely used in the learning process. The purpose of this study is to develop android-based learning media as an alternative to science learning media in elementary schools. The research method used in this study is Research and Development (R&D) which refers to the model developed by Sugiyono with 10 steps. Data collection instruments in the form of observations, validation sheets and student response questionnaires. The subjects of the study were students in grade 4 totaling 30 students at SDN 01 Kalibening Raya. The results of this study 0020 application named MEDIFORA with a feasibility rate by experts of 76.32% were declared feasible because they exceeded 61%. The effectiveness of the MEDIFORA Application seen from student learning results is obtained that MEDIFORA is effective which is shown by the level of completeness of student learning of 80%. Based on these results, it can be concluded that the MEDIFORA application can be used as an alternative science learning media for life cycle materials in grade 4 elementary schools.